1995
DOI: 10.1180/minmag.1995.059.397.08
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mineral chemistry in amphibolites from the western Tauern Window (Eastern Alps), and P-T deformation paths of the Alpine greenschist-amphibolite facies metamorphism

Abstract: Amphibolites in the Mesozoic part of the parautochthonous Lower Schieferh~ille (LSH), the allochthonous Upper Schieferh~ille (USH) and the overlying Austroalpine basement (AA) in and around the western Tauern Window (Eastern Alps) suffered a progressive Alpine deformation. Lineations and foliations L1-S1, L2-$2 defined by preferentially oriented (Na-Ca) amphiboles as well as F3 folds and further foliations Smy I and $4 in the metabasites are structures of successive deformational stages with a constant W-E mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Holland and Richardson, 1979;Triboulet et al, 1992;Okamoto and Toriumi, 2004). For example, amphibole zonation and related thermobarometry has enabled reconstruction of coherent P-T paths in metabasites from the Barrovian-type metamorphic zones of the Scottish Dalradian (Zenk and Schulz, 2004), and given a deeper insight into the Alpine metamorphic evolution and refinement of prograde-retrograde P-T-deformation paths in the western Tauern Window, Eastern Alps (Schulz et al, 1995) or in the Toulepleu-Ity region, Ivory Coast (Triboulet and Feybesse, 1998). It also led to the identification of twostage burial episodes (successive subduction-uplift then collision-uplift processes) and a complex decompression history during Variscan metamorphism in the Baie d'Audièrne region and Ile de Groix in Brittany, western France (Lucks et al, 2002;Schulz et al, 2001) or the Maures massif, SE France (Bellot et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Holland and Richardson, 1979;Triboulet et al, 1992;Okamoto and Toriumi, 2004). For example, amphibole zonation and related thermobarometry has enabled reconstruction of coherent P-T paths in metabasites from the Barrovian-type metamorphic zones of the Scottish Dalradian (Zenk and Schulz, 2004), and given a deeper insight into the Alpine metamorphic evolution and refinement of prograde-retrograde P-T-deformation paths in the western Tauern Window, Eastern Alps (Schulz et al, 1995) or in the Toulepleu-Ity region, Ivory Coast (Triboulet and Feybesse, 1998). It also led to the identification of twostage burial episodes (successive subduction-uplift then collision-uplift processes) and a complex decompression history during Variscan metamorphism in the Baie d'Audièrne region and Ile de Groix in Brittany, western France (Lucks et al, 2002;Schulz et al, 2001) or the Maures massif, SE France (Bellot et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Baker, 1985;Fettes et al, 1985;Dempster and Harte, 1986;Harte, 1988;Dempster and Bluck, 1995) has not been matched by studies of the mineral chemistry and metamorphism of the Dalradian metabasites (Wiseman, 1934;Laird and Albee, 1981;Sivaprakash, 1981Sivaprakash, , 1982. It has been demonstrated that metabasite mineral assemblages with growth-zoned Ca-amphiboles have a high potential for metamorphic pressure-temperature path reconstruction and give considerable insight to the tectonothermal evolution (Triboulet and Audren, 1988;Triboulet, 1992;Triboulet et al, 1992;Schulz et al, 1995Schulz et al, , 2001. A systematic microstructural, mineral chemical and thermobarometric study on metabasite Ca-amphibolebearing assemblages throughout the zones should give a complementary insight to the nature of the Barrovian metamorphism in the Dalradian and its controversial aspects.…”
Section: Introductionmentioning
confidence: 99%
“…A similar tectonic model involving two successive phases of burial/exhumation, followed by late uplift has been proposed for other parts of the Variscan belt as the French Massif Central (Faure et al 1997), the Vosges massif (Schaltegger et al 2000), the south Brittany and the Ile de Groix (Schulz et al 2001b). In addition, similar Alpine two-stage successive subduction-uplift then collision-uplift processes have been recognised in metamorphic rocks of the Betic Cordilleras (Puga et al 1989) and metabasites from the western Tauern Window in the Eastern Alps (Schulz et al 1995). It is the case of La Brévenne (Leloix et al 1999) and the south Limousin areas Bellot 2001).…”
Section: Resultsmentioning
confidence: 81%